2012
DOI: 10.1002/14651858.cd004945.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour for improving birth outcomes for women at or beyond term

Abstract: Background As a pregnancy continues beyond term the risks of babies dying inside the womb or in the immediate newborn period increase. Whether a policy of labour induction at a predetermined gestational age can reduce this increased risk is the subject of this review. Objectives To evaluate the benefits and harms of a policy of labour induction at term or post-term compared with awaiting spontaneous labour or later induction of labour. Search methods We searched the Cochrane Pregnancy and Childbirth Group’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 84 publications
7
106
1
8
Order By: Relevance
“…24 Another study has indicated that induction may increase the risk of caesarean section if performed before the 40th week of gestation, but it has no effect or actually lowers the risk if performed after the 40th week. 25,26 while some recent reviews regarding IOL and its effect on Cesaerean section rates do indicate that there is no significant increase in IOL rates but on the contrary there can be a reduction in Caeserean section rates with IOL.…”
Section: Discussionmentioning
confidence: 99%
“…24 Another study has indicated that induction may increase the risk of caesarean section if performed before the 40th week of gestation, but it has no effect or actually lowers the risk if performed after the 40th week. 25,26 while some recent reviews regarding IOL and its effect on Cesaerean section rates do indicate that there is no significant increase in IOL rates but on the contrary there can be a reduction in Caeserean section rates with IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Note that to obtain the utility scores for the mother's perspective only the first term is used for each state, whereas for the utilities from the baby's perspective only the second term is used for each state. (2,3,1,0.5,1.5, 2,1.5,2,3), d=c (NA,5,4,2,3,1,3,4,5)) DOI: 10.3310/hta20650 HEALTH TECHNOLOGY ASSESSMENT 2016 VOL. 20 NO.…”
Section: Appendix 3 Reference List For Excluded Studiesmentioning
confidence: 99%
“…Induction for 'post- antenatal fetal monitoring should be made available. 2 Induction at or beyond 41 weeks is thus phrased as an option, not a practice to be strongly encouraged for all women, and induction for postmaturity before 41 weeks is not recommended and shows no benefits. As induction of labour with oxytocin is associated with a greater need for epidural analgesia, 3 it is presumably more painful and thus should be avoided unless necessary.…”
Section: Induction Of Labourmentioning
confidence: 99%